2013
DOI: 10.1186/1472-6882-13-75
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and haematological assessment of toxic effects of the leaf ethanol extract of Petroselinum crispum (Mill) Nyman ex A.W. Hill (Parsley) in rats

Abstract: BackgroundPetroselinum crispum, a bright green biennial shrub is widely used traditionally as a food additive and herbal remedies for many ailments. This study therefore aimed to assess the toxic effects of its leaf extract using some biochemical, haematological parameters.MethodsThe toxic effects were assessed by quantifying liver enzymes such as serum aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase (ALP), total serum protein and liver weight. Effects on haematological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
3
29
3
1
Order By: Relevance
“…In their study they found that oral administration with Isoniazid drug resulted in occurrence of physiological or hypochromic anemia which monitored from the significant decrease in hemoglobin content, RBCs count (erythrocytopenia), hematocrite value, MCH, and MCHC; also, thrombocytopenia (decrease in platelets count) and leucopenia (reduction of TLC) were recorded in compare to control group. Our results are also in accordance with the reports of [21][22][23][24] who reported that chronic application of Isoniazid induces a reduction in the number of platelets, RBCs and leukocytes through the induced oxidative stress, which might affect their life expectancy, induce an apoptosis and thereby ultimately reduce the number of these cells in the blood.…”
Section: Analysis Of Blood Samplesupporting
confidence: 93%
“…In their study they found that oral administration with Isoniazid drug resulted in occurrence of physiological or hypochromic anemia which monitored from the significant decrease in hemoglobin content, RBCs count (erythrocytopenia), hematocrite value, MCH, and MCHC; also, thrombocytopenia (decrease in platelets count) and leucopenia (reduction of TLC) were recorded in compare to control group. Our results are also in accordance with the reports of [21][22][23][24] who reported that chronic application of Isoniazid induces a reduction in the number of platelets, RBCs and leukocytes through the induced oxidative stress, which might affect their life expectancy, induce an apoptosis and thereby ultimately reduce the number of these cells in the blood.…”
Section: Analysis Of Blood Samplesupporting
confidence: 93%
“…For example, in a study conducted on pigs, Chaudhary et al (1986) found that photodermatitis occurred due to the presence of furocoumarins. Moreover, Awe and Banjoko (2013) reported that P. crispum ethanol leaf extract exhibited hepatotoxic and nephrotoxic activities. A study on P. crispum oil (0.6 ml/kg body weight) showed protective activity against zearalenone-induced reproductive toxicity and improved testosterone levels in mature male mice (Salah-Abbès et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Parsley (Petroselinum crispum), a bright green, a biennial shrub that has been employed in the pharmaceutical, perfume, and cosmetic industries [68], and widely used traditionally as a food additive and herbal remedies for many ailments [69]. It is a member of the Apiaceous family [68].…”
Section: Parsley (Petroselinum Crispum)mentioning
confidence: 99%